Characterization of different types of anxiety disorders in relation to structural integration of personality and adverse and protective childhood experiences in psychotherapy outpatients - a cross-sectional study - Nowak, Jonathan; Nikendei, Christoph; Dönnhoff, Ivo; Orth, Maximilian; Friederich, Hans-Christoph; Kindermann, David (BMC psychiatry, 2023)
Current research has emphasized the role of structural integration of personality and childhood experiences for the understanding of anxiety disorders. In this study, we examined the relationship between anxiety disorders (generalized anxiety disorder vs. panic disorder vs. phobic disorders), the level of structural integration of personality, and negative and protective childhood experiences at the beginning of outpatient psychodynamic psychotherapy treatment. Differences were characterized in comparison to patients with no anxiety disorders.
Veröffentlicht: 12. Juli 2023
Gesehen am 17.08.2023